2013
DOI: 10.1097/mpg.0b013e3182a934c7
|View full text |Cite
|
Sign up to set email alerts
|

Calretinin, β‐Tubulin Immunohistochemistry, and Submucosal Nerve Trunks Morphology in Hirschsprung Disease

Abstract: Calretinin is a reliable marker of the presence of ganglion cells, and, together with nerve hypertrophy, it helps to identify the transition zone. Length and nerve size of proximal segment in resected specimen did not affect the postsurgical intestinal function. Reduced β-tubulin expression along the entire colonic tract, included proximal ganglionic segments, may represent a potential impairing factor for the enteric neural transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 38 publications
1
22
1
Order By: Relevance
“…Although there was a gradual increase of the mucosal calretinin staining in the TZ in a majority of cases, a substantial variation of staining around the circumference at the same distance and along the distance in the probable NZ was noted. Our findings are consistent with previous studies that demonstrate the irregular nature of the TZ 18 and confirm the difficulty of defining a clinically relevant TZ. For now, as the boundaries of the TZ cannot be accurately defined preoperatively using endoscopic mucosal biopsies, intraoperative frozen section examination of the proximal surgical margin to exclude major histopathological features recognized in the TZ, as recommended by other authors, will be prudent.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Although there was a gradual increase of the mucosal calretinin staining in the TZ in a majority of cases, a substantial variation of staining around the circumference at the same distance and along the distance in the probable NZ was noted. Our findings are consistent with previous studies that demonstrate the irregular nature of the TZ 18 and confirm the difficulty of defining a clinically relevant TZ. For now, as the boundaries of the TZ cannot be accurately defined preoperatively using endoscopic mucosal biopsies, intraoperative frozen section examination of the proximal surgical margin to exclude major histopathological features recognized in the TZ, as recommended by other authors, will be prudent.…”
Section: Resultssupporting
confidence: 93%
“…Irregular distribution of the ganglion cells, including the finding of submucosal hyperganglia, and varying cellularity of myenteric plexus ganglia in the TZ are well described. 10,18 In our study, no distinct pattern was observed in the order of submucosal and myenteric ganglion cells that were first detected. Also, the distance between the beginning of the TZ and the most distal ganglion cells varied.…”
Section: Discussioncontrasting
confidence: 64%
“…Since the introduction of acetylcholinesterase staining, different types of neurones and ganglia in the submucosal and myenteric plexuses and various stains that mark neurones and nerve fibres have been identified . Immunohistochemical markers tested in cases of HD include: RET oncoprotein, neurone‐specific enolase, calretinin, MAP2, peripherin, NeuN and nNOS for the detection of ganglion cells; and GLUT1, S100, GFAP, NGFR and beta‐tubulin for the detection of nerve fibres . The aim of this study was to identify a method for the reliable diagnosis of HD using immunohistochemical staining that combined detection of ganglia (MAP2 and calretinin) and the evaluation of nerve fibres (S100 and GLUT1).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Immunohistochemical markers tested in cases of HD include: RET oncoprotein, neurone-specific enolase, calretinin, MAP2, peripherin, NeuN and nNOS for the detection of ganglion cells; and GLUT1, S100, GFAP, NGFR and beta-tubulin for the detection of nerve fibres. [19][20][21][22][23][24][25][26][27][28][29] The aim of this study was to identify a method for the reliable diagnosis of HD using immunohistochemical staining that combined detection of ganglia (MAP2 and calretinin) and the evaluation of nerve fibres (S100 and GLUT1). Such an immunohistochemical diagnostic panel offers several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Morris et al [35] state that calretinin immunohistochemistry may be superior to AChE in the context of total aganglionosis, superficial biopsies, and prematurity. Volpe et al [36] describe that together with nerve hypertrophy, calretinin is a reliable marker for the transition zone. Uniformly, all authors conclude that calretinin immunohistochemistry is a reliable modality to diagnose HD and is equivalent if not superior to AChE, with a sensitivity of 93.3% and specificity of 100%.…”
Section: Rectal Biopsiesmentioning
confidence: 99%